2017
DOI: 10.1177/0960327116688070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resveratrol and tetracycline on the subacute paraquat toxicity in mice

Abstract: Paraquat (PQ) is a nonselective bipyridyl herbicide widely used in agriculture to control weeds, but its accidental, occupational, or intentional exposure in humans is known to cause pneumo- and neurotoxicity which may proves fatal. Oxidative stress is reported as an underlined mechanism of PQ-induced toxicity in alveolar cells, neurons, and astroglia. PQ generates superoxides both through electron transport reaction (ETC) with nicotinamide adenine dinucleotide–dependent oxidoreductase and by the redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 55 publications
(63 reference statements)
1
10
0
Order By: Relevance
“…On the other hand, MDA is one of the most commonly used indicators of lipid peroxidation: the process that has been implicated in several deleterious effects such as increased membrane rigidity, osmotic fragility, and reduced mitochondrial survival [ 39 ]. We and others demonstrated lipid peroxidation as a biomarker of PQ hepatic toxicity [ 37 , 40 , 41 ]. It was demonstrated that Res can modulate cellular redox in several models of liver injury [ 11 13 ] and in subacute PQ toxicity in mice [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, MDA is one of the most commonly used indicators of lipid peroxidation: the process that has been implicated in several deleterious effects such as increased membrane rigidity, osmotic fragility, and reduced mitochondrial survival [ 39 ]. We and others demonstrated lipid peroxidation as a biomarker of PQ hepatic toxicity [ 37 , 40 , 41 ]. It was demonstrated that Res can modulate cellular redox in several models of liver injury [ 11 13 ] and in subacute PQ toxicity in mice [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…We and others demonstrated lipid peroxidation as a biomarker of PQ hepatic toxicity [ 37 , 40 , 41 ]. It was demonstrated that Res can modulate cellular redox in several models of liver injury [ 11 13 ] and in subacute PQ toxicity in mice [ 41 ]. Similarly, MK has been shown to diminish oxidative stress markers and enhance antioxidants in rat liver [ 16 , 17 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animals treated with PQ tend to succumb (Bonilla et al., 2006; Martínez‐Lendech et al., 2018; Sittipunt, 2005). Antioxidants protect against PQ‐induced oxidative toxicity (Bonilla et al., 2006; Satpute et al., 2017; Thiruchelvam et al., 2005), while PQ affords protection in individuals infected with pathogens that produce antioxidants to avoid the host pro‐oxidant defenses (Medina‐Gómez et al., 2018). Based on the aforementioned evidence, PQ appears to cause oxidative stress in T. molitor .…”
Section: Discussionmentioning
confidence: 99%
“…In the current ,an increase signi cantly in the activities of serum ALT and AST was observed following treatment with difenoconazole, which have been attributed to leakage of cellular enzymes in circulation as a result of loss function integrity of cell membrane of hypatocytes [ Navaro et al .,1993 andOzer et al .,2008] A number of chemical including agro-pesticides and various environmental pollutanta can severe cellular damage in different organs in the body .This occurred through metabolic activation to highly reactive substances such as free radicals (Satpute et al, 2017).…”
Section: Parametersmentioning
confidence: 99%